Pengaruh Asimetris Nilai Tukar terhadap Ekspor: Kasus Ekspor Industri Indonesia Tahun 2007-2016 - Welldy, Welldy; Widyawati, Diah (UI Scholars Hub, 2019)
This study aims to see whether appreciation and depreciation have asymmetric impact on Indonesia's industrial exports and which impact is greater. The researcher uses disaggregated panel of Indonesian industrial product export HS Code 10 digit level with all partner country of export. Acquired domestic appreciation has a negative impact and depreciation has a positive impact on exports, where the impact is both asymmetric. The negative impact of appreciation is greater than the positive impact of depreciation. While domestic appreciation, export demand is more elastic due to competition in international markets which makes other countries turn to domestic products in their destination countries or even import goods from other countries and export supply less elastic or less elasticity due to avoiding risk due to reduced export demand even though the price of imported goods is cheaper. Meanwhile, when the depreciation due to competition in the international market resulted in an increase in elasticity of export demand is smaller than when domestic appreciation occurs. In addition, the export supply become more elastic as the industry sees imported goods becoming more expensive which can increase production costs.